The philosophy of higher education of the 21st century - Isahak, Aldila (Institut Penyelidikan Pendidikan Tinggi Negara (IPPTN), 2007)
This article briefly looked at the socio-politico-economic context of ancient Chinese,Greeks, Medieval Europe, the Muslims during the Medieval period and Postmodernism. The political thought of Confucius, Plato, St. Augustine, al-Farabi were surveyed in order to put into perspective the philosophy of higher education from 5th century BC to the 21st century AD.